Metabolic Profile of Sow Blood Serum after Weaning - Nadezhda Vladimirovna Bogolyubova; Roman Anatolievich Rykov; Sergei Yurevich Zaitsev (Veterinary Medicine International)
The aim of our research was to determine the content of protein, carbohydrate, lipid, and mineral metabolites, as well as an antioxidant status of the sow’s blood after weaning and to calculate the correlation between these parameters. The experiment was carried out on twenty clinically healthy crossbred sows (Yorkshire × Landrace). Twenty sows were allocated to one of two groups: (1) 1 day after weaning (group 1, n = 10) and (2) 8 days after weaning (group 2, n = 10). The basis of the sow diet was SK-1 compound feed, balanced in terms of nutrients and energy in accordance with modern standards and the recommended feeding regimen. Sows blood samples were taken and analyzed for the metabolites of nitrogenous, carbohydrate-lipid, and mineral metabolism and indicators of antioxidant status. The results showed that, in group 2, the total protein content was 89.07 g/l, which is 10.2% higher than that in group 1 (p<0.05); it was mainly achieved due to the globulin fraction. The urea increased by 19.1% (p<0.05), but the concentrations of magnesium and chlorides decreased by 20.2% (p<0.01) and 5.43% (p<0.05), as well as the alkaline phosphatase and ALT activities decreased by 42.5% (p<0.05). Strong positive correlations of the ceruloplasmin with total protein (0.672) and very strong with globulins (0.780) were observed. There was a strong negative correlation between the AST activity and the TBA-AP content, as well as the values of phospholipids and TAWSA. There are moderate negative correlations of the TBA-AP with magnesium, TAWSA and ALT activity, and moderate positive correlations of the TBA-AP with total protein, albumin, triglycerides, and cholesterol. The revealed tendencies and dependencies will serve as the theoretical basis for the development of practical methods for regulating the level of free-radical reactions.